Encounters between foreign relations law and international law : bridges and boundaries - Aust, Helmut Philipp, 1980-; Kleinlein, Thomas (Cambridge University Press, 2021)
"Foreign relations law is developing very dynamically and expanding its horizons while its relationship with public international law is notoriously complex. Like an interface, foreign relations law addresses multiple and diverse questions about how the 'domestic' relates to the 'international' sphere. This volume takes a fresh look at the 'bridges' and 'boundaries' between public international law and foreign relations law"--